The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.22608/apo.2016126
|View full text |Cite
|
Sign up to set email alerts
|

Post-Vitrectomy Endophthalmitis in Victoria, Australia

Abstract: Treatment of diseases with gene therapy is advancing rapidly. The use of gene therapy has expanded from the original concept of replacing the mutated gene causing the disease to the use of genes to control nonphysiological levels of expression or to modify pathways known to affect the disease. Genes offer numerous advantages over conventional drugs. They have longer duration of action and are more specific. Genes can be delivered to the target site by naked DNA, cells, nonviral, and viral vectors. The enormous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…Furthermore, the magnitude of scAAV5 transduction in the TM and Schlemm’s canal was greater than that of the other serotypes. In contrast, in cultured human and porcine TM cells, the transduction efficiency of scAAV5 was greater than that of scAAV2; thus, scAAV tropism may differ among species 25 . However, no study has evaluated recombinant AAV8 or scAAV8 transduction in anterior-segment structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the magnitude of scAAV5 transduction in the TM and Schlemm’s canal was greater than that of the other serotypes. In contrast, in cultured human and porcine TM cells, the transduction efficiency of scAAV5 was greater than that of scAAV2; thus, scAAV tropism may differ among species 25 . However, no study has evaluated recombinant AAV8 or scAAV8 transduction in anterior-segment structures.…”
Section: Discussionmentioning
confidence: 99%
“…reported that intracameral injection of scAAV2-GFP resulted in persistent gene expression in the TM for more than 2 years. Also, transduction of scAAV2 has been demonstrated in primary human TM and porcine-perfused organ cultures 25 . Intracameral injection of scAAV5 in live rats resulted in greater transduction in the TM than did scAAV2 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TM is most likely transduced as the particles get circulated out of the vitreous chamber. The TM and the ONH are commonly under investigation to better understand and treat glaucoma [36][37][38]. Specific to the TM, researchers have been investigating and developing gene therapy approaches that reduce ocular pressure [37].…”
Section: Supporting Informationmentioning
confidence: 99%
“…The TM and the ONH are commonly under investigation to better understand and treat glaucoma [36][37][38]. Specific to the TM, researchers have been investigating and developing gene therapy approaches that reduce ocular pressure [37]. As glaucoma is a multifaceted disease, researchers have also developed a method of small molecule delivery to the ONH of rats that allows for exploration of molecular and cellular pathways involved in neuropathies and treatment screening [38].…”
Section: Supporting Informationmentioning
confidence: 99%